Secondary metabolites of Alternaria: A comprehensive review of chemical diversity and pharmacological properties - Zhao, Shiqin; Li, Juan; Liu, Jinping; Xiao, Shaoyujia; Yang, Sumei; Mei, Jiahui; Ren, Mengyao; Wu, Shuzhe; Zhang, Hongyuan; Yang, Xiliang (Frontiers in Microbiology, 2023)
Fungi are considered to be one of the wealthiest fountainheads of bio-metabolites that could be employed for yielding novel biomedical agents. Alternaria, including parasitic, saprophytic, and endophytic species, is a kind of dark fungi that could produce a broad array of secondary metabolites (SMs) widely distributed in many ecosystems. They are categorized into polyketides, nitrogen-containing compounds, quinones, terpenes, and others based on the unique structural features of these metabolites. New natural products derived from Alternaria exhibit excellent bioactivities characterized such as antibacterial, antitumor, antioxidative, phytotoxic, and enzyme inhibitory properties etc. Thus, the bio-metabolites of Alternaria species are significant meaningful for various pharmaceutical, industrial, biotechnological, and medicinal applications. To update the catalog of secondary metabolites synthesized by Alternaria fungi, 216 newly described metabolites isolated from Alternaria fungi were summarized with their diverse chemical structures, pharmacological activity, and the possible biosynthetic pathway as well. With that, possible insights, avenues, challenges for the future research and development of Alternaria are discussed.